LEGAL PROTECTION OF CONSUMERS THROUGH HALAL CERTIFICATION ON PROCESSED FOOD PRODUCTS IN PALU CITY - Marzuki Marzuki (Hunafa: Jurnal Studia Islamika, 2020)
This study discusses legal protection for Muslim consumers through Halal certification in processed food products in Palu. This is based on the writer's concern watching case after case that occurred in the community. With a variety of excuses and interests, the community as consumers become victims of the irresponsible behavior of processed food producers. This research is a normative study combined with empirical research to find out various factors that influence the realization of legal protection for Muslim consumers for processed food products in Palu. Namely: legal substance, Law enforcement officials Related to Halal Certification, Community Legal Culture and Supporting Facilities. The results showed that the four influential factors had not played their role maximally so that the conclusion was drawn that the legal protection of Muslim consumers through halal certification on processed food products in Palu had not been effective.